Pengembangan Instrumen Penilaian Pemahaman Konsep IPA Terintegrasi Erupsi Gunung Berapi - Rizki Arumning Tyas; P Pujianto; D Dalinem (Faktor : Jurnal Ilmiah Kependidikan, 2023)
The successful implementation of disaster risk reduction efforts and its integration with science learning can be measured using a measuring instrument in the form of a test instrument that specifically measure the achievement of student’s concept mastery of disaster and student’s preparedness of disaster. This study aimed to develop an instrument to assess the risk reduction efforts of volcanic eruption in natural science learning and determine the validity and reliability of these instruments. The development of the instrument uses a 4-D model from Thiagarajan, consist of Define, Design, Develop, and Disseminate. The instruments developed include the questions of mastery assessment concepts of volcanic eruption and its effort to reduce the disaster risk and the questions of disaster preparedness assessment. Testing the validity and reliability of the instrument was conducted empirically on 210 students. Data analysis was performed descriptively using the QUEST program. The study produced 35 items of valid concept mastery assessment items that had a very high level of reliability with the value of reliability of estimate of 0.95 and 15 items of valid disaster preparedness assessment items that had a very high level of reliability with the value of reliability of estimate of 0.98.